Characterization of a Double Mesospheric Bore Over Europe. Issue 9 (29th September 2017) - Smith, Steven M.; Stober, Gunter; Jacobi, Christoph; Chau, Jorge L.; Gerding, Michael; Mlynczak, Martin G.; Russell, James M.; Baumgardner, Jeffrey L.; Mendillo, Michael; Lazzarin, Monica; Umbriaco, Gabriel
Abstract: Observations of a pair of mesospheric bore disturbances that propagated through the nighttime mesosphere over Europe are presented. The observations were made at the Padua Observatory, Asiago (45.9°N, 11.5°E), by the Boston University all‐sky imager on 11 March 2013. The bores appeared over the northwest horizon, approximately 30 min apart, and propagated toward the southeast. Using additional satellite and radar data, we present evidence indicating the bores originated in the mesosphere from a single, larger‐scale mesospheric disturbance propagating through the mesopause region. Furthermore, the large‐scale mesospheric disturbance appeared to be associated with an intense weather disturbance that moved southeastward over the United Kingdom and western Europe during 10 and 11 March. Key Points: Rare double mesospheric bore observed Both bores appeared to be associated with, and originated from, a single larger‐scale mesospheric gravity wave disturbance The event suggested that wave energy was transported from the Earth's surface to near 100 km in altitude Plain Language Summary: A large wave disturbance occurred in the upper atmosphere over western Europe in March 2013 and appeared to be associated with a large storm system that brought cold weather and snow to the UK and western Europe. The disturbance, called a bore, occurred in the Earth's mesosphere an altitude of 90‐‐100 km. Little is known about the origin of mesospheric bores, but it would appear that surface weather activity may be a contributor to their formation in some cases.